Sistemas de equações lineares: uma proposta de atividades com abordagem de diferentes registros de representação semiótica - Freitas, Nilza Aparecida de (2013)
This research aims to develop, implement and analyze a didactic sequence to investigate how the high school students of a public school in the city of São This research aims to develop, implement and analyze a didactic sequence to the proposed approach promotes the conversion and treatment of Registers of Semiotic Representation from Duval (2009). Therefore, we have presented an instructional sequence so that students can determine the solution of linear systems of two equations in the proposed activities and in connection with the different forms of representation: algebraic, graphical and natural language. On graphic record was used a software named Geogebra. After the application with methodological support of Didactic Engineering from Artigue (2010), we analyzed the protocols of six students participating in three sessions. The results reveal how evolution occurred from these students in solving linear systems, provided by the conversion activity and treatment the records of Semiotic Representation. It is hoped that this research will contribute to the learning of students in linear systems theme and encourage other studies of this mathematical object in research of Mathematics Education